When the PCAOB talks, who listens? Evidence from stakeholder reaction to GAAP-deficient PCAOB inspection reports of small auditors - Abbott, Lawrence J. (Institutional Knowledge at Singapore Management University, 2013)
Section 104 of the Sarbanes-Oxley Act (SOX) created the Public Company Accounting Oversight Board (PCAOB). The PCAOB conducts inspections of registered public accounting firms that provide audits for publicly traded companies. The results of the inspection process are summarized in publicly available reports at the PCAOB website. Using these reports, we categorize the inspection reports into three levels of increasing severity: clean, GAAS-deficient, and GAAP-deficient. We examine the potential use of GAAP-deficient PCAOB inspection reports as perceived audit quality signals for the clients of GAAP-deficient auditors that are inspected on a triennial basis by the PCAOB. Our investigation is predicated on the notion that audit quality is generally not directly observable. Thus, the clients of these auditors may seek to signal their desire for audit quality by dismissing their GAAP-deficient auditors. Our results suggest that the clients of GAAP-deficient, triennially inspected auditors are more likely to dismiss these auditors in favor of triennially inspected auditors that are not GAAP-deficient. In addition, we find that greater agency conflicts, the presence of an independent and expert audit committee, and outside blockholdings magnify this effect. Interestingly, we find no evidence that the clients use GAAP-deficient reports to procure a subsequent-year audit fee discount or more favorable going-concern auditor reporting treatment. Our evidence indicates that PCAOB inspection reports created heterogeneity in auditor brand name among a group of non-Big N/non-national auditors that did not previously exist and are universally treated by prior research as “other auditors.”